2016
DOI: 10.1161/jaha.115.003163
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke or Systemic Embolism After Transseptal Ablation of Arrhythmias in Patients With Cardiac Implantable Electronic Devices

Abstract: BackgroundIncidental mobile thrombi are commonly found on endovascular leads of cardiac implantable electronic devices (CIEDs). Transseptal puncture for catheter ablation of arrhythmia poses a risk for paradoxical embolism. We examined risk of ischemic stroke, transient ischemic attack (TIA), or systemic embolism after transseptal ablation in patients with and without CIEDs.Methods and ResultsUsing a national administrative claims database, 31 720 patients who underwent a transseptal catheter ablation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…The PROTECT AF reported 7% iASD after Watchman implant but none suffered from systemic emboli at 12-month follow-up [17]. In contrast to a cross-sectional study derived for a large national database, Madhavan et al [20] found that patients with preexisting CIEDs who had undergone a transseptal procedure were at a higher risk of stroke with an overall risk of systemic embolism around 2 per 100 person-year. Noteworthy that the risk was mitigated by anticoagulation.…”
Section: Emboli Through the Defectmentioning
confidence: 96%
See 1 more Smart Citation
“…The PROTECT AF reported 7% iASD after Watchman implant but none suffered from systemic emboli at 12-month follow-up [17]. In contrast to a cross-sectional study derived for a large national database, Madhavan et al [20] found that patients with preexisting CIEDs who had undergone a transseptal procedure were at a higher risk of stroke with an overall risk of systemic embolism around 2 per 100 person-year. Noteworthy that the risk was mitigated by anticoagulation.…”
Section: Emboli Through the Defectmentioning
confidence: 96%
“…Most of the persistent iASD is relatively small, with an average size of 4.6-6.0 mm, and thus without suggestive high-risk PFO characteristics. Further, majority of AF patients would need anticoagulation anyway and that seems to offset the risk of stroke [20]. However, this question is relevant in patients with CHA 2 DS 2 -VAS 2 score of 0-1 when anticoagulation is generally discontinued few months postablation.…”
Section: Emboli Through the Defectmentioning
confidence: 99%
“…To date, the OLDW has sought to bring together diverse practitioners to collaborate on agenda-setting related to clinically relevant questions and translation of these results into practical changes that directly impact patient care. From the outset, the OLDW has encouraged clinical questions that promote observational studies that could “achieve results as close as possible to the estimate one would get from a randomized trial designed to answer the same question.” 4 Indeed, investigations of patients with heart failure, 9 , 10 stroke, 11 , 12 diabetes, 13 and atrial fibrillation, 14 , 15 among others, have been successfully completed, and such results have been valuable at informing clinical practice patterns. As a major goal of the OLDW is promoting translation of research into practice, the clinical question regarding EN use in ALS seemed to be an ideal one to be answered by OLDW.…”
Section: Discussionmentioning
confidence: 99%
“…Пациенты разделяются на приверженных и не приверженных к лечению в соответствии с пороговым значением (выше или ниже порога) числа дней адекватного приема лекарств по отношению к продолжительности избранного периода наблюдения. Как правило, в исследованиях приверженности к пероральным антикоагулянтам [13][14][15][16] и другим методам постоянной терапии приверженными к лечению считали больных, которые принимали назначенный препарат ≥80 % дней в течение, например, 3, 6 мес, 1 года. Пороговое значение ≥80 % достаточно условно и впервые появилось в исследованиях антигипертензивной терапии, проведенных еще в 70-х годах XX века.…”
Section: проблема низкой приверженности к антикоагулянтной терапии в unclassified
“…Представляется очевидным, что пациенты должны принимать назначенные лекарства, чтобы получать от них пользу. Практически во всех исследованиях высокая приверженность к рекомендованному лечению снижала смертность, риск неблагоприятных клинических исходов, частоту повторных госпитализаций, затраты системы здравоохранения [13][14][15][16][17][18]. Современные когортные исследования, в которых изучалось влияние приверженности к ППОАК на исходы у пациентов с ФП, как правило, имели ретроспективный характер, но отличались большими размерами выборки.…”
Section: проблема низкой приверженности к антикоагулянтной терапии в unclassified